2019
DOI: 10.2478/sjdv-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of Treatment-Resistant Alopecia Areata with Platelet Rich Plasma: A Case Series

Abstract: Introduction. Alopecia areata (AA) is an autoimmune disease-causing non-scarring alopecia. It is usually treated with immunosuppressive agents, to which some patients fail to respond adequately. Material and Methods. Three patients with AA refractory to standard therapy were treated with intra-dermal injection of autologous platelet rich plasma (PRP) every four weeks. Results. All three patients showed remarkable improvement after multiple sessions of PRP treatment. Conclusion. Autologous PRP is safe and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…In literature there are few clinical trials discussing treatment of AA with PRP [9], [16], [17], [18], [19], [20], [21], [22], [23], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35] and most of them agree with our results. On the other hand, D'Ovidio and Roberto in 2014 showed restricted usefulness of PRP in long standing cases (more than 2 years) and proposed that PRP effect may be held in reserve for mild cases [44].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In literature there are few clinical trials discussing treatment of AA with PRP [9], [16], [17], [18], [19], [20], [21], [22], [23], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35] and most of them agree with our results. On the other hand, D'Ovidio and Roberto in 2014 showed restricted usefulness of PRP in long standing cases (more than 2 years) and proposed that PRP effect may be held in reserve for mild cases [44].…”
Section: Discussionsupporting
confidence: 90%
“…These GFs are believed to stimulate stem cells sited in HF at the bulge areas leading to growth of fresh follicles and enhancing angiogenesis [13], [15]. Despite of its promising results in AA, a paucity of randomized controlled clinical trials had been published to assess the efficiency of PRP in management of AA [9], [13], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], 29], [30], [31], [32], [33], [34], [35]. Photobiomodulation (PBM), or low-level laser (or) light therapy (LLLT) is using red light (600-700 nm) or near infrared (700 nm-1000+nm) which is obtained from 5 to 500 mW light-emitting diode (LED) source [36], [37].…”
Section: Introductionmentioning
confidence: 99%
“…The PRP preparation protocols of included studies are demonstrated in Tables 3 , 4 . Regarding the centrifugation method, there were 13 studies using single spin method ( 33 , 34 , 36 , 39 , 43 , 47 , 49 , 52 , 53 , 58 , 60 , 63 , 64 ), 10 using double spin method ( 35 , 37 , 38 , 40 42 , 45 , 46 , 51 , 56 ), and eight provided no information ( 44 , 48 , 54 , 55 , 57 , 59 , 61 , 62 ). Several types of PRP activators were used; seven studies used calcium chloride ( 37 , 38 , 41 , 45 , 46 , 49 , 60 ), four used calcium gluconate ( 33 , 34 , 36 , 42 ), one used calcium carbonate ( 52 ), two did not use any activators ( 48 , 53 ), and 17 provided no information ( 35 , 39 , 40 , 43 , 44 , 47 , 51 , 54 59 , 61 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding treatment protocol, most studies used three or four treatment sessions, with 15 using three sessions ( 33 , 34 , 38 , 40 42 , 45 , 47 , 50 , 53 , 54 , 56 , 60 , 63 , 64 ), six using four sessions ( 35 , 36 , 39 , 49 , 57 , 59 ), two treated until a satisfactory response was obtained ( 51 , 61 ), and the remaining studies used different number of sessions. Our included studies selected different treatment intervals, with the most common interval being 4 weeks, selected by 17 studies ( 33 , 34 , 36 , 38 , 40 42 , 44 , 45 , 47 , 51 , 55 , 56 , 58 , 60 , 62 , 64 ); five studies selected 3 weeks ( 35 , 39 , 50 , 57 , 59 ), four selected 2 weeks ( 37 , 46 , 49 , 52 ), one selected 1 week ( 43 ), and four selected interval of ≥ 6 weeks ( 53 , 54 , 62 , 63 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation